Exhaled Breath Condensate: A Non-Invasive Source for Tracking of Genetic and Epigenetic Alterations in Lung Diseases - Somayeh Kezeminasab; Babak Emamalizadeh; Maryam Khoubnasabjafari; Abolghasem Jouyban (Tabriz University of Medical Sciences, 2021)
Lung diseases have been recognized as an extensive cause of morbidity and mortality in the worldwide. The high degree of clinical heterogeneity and nonspecific initial symptoms of lung diseases contribute to a delayed diagnosis. So, the molecular and genomic profiling play a pivotal role in promoting the pulmonary diseases. Exhaled breath condensate (EBC) as a novel and potential method for sampling the respiratory epithelial lining fluid is to assess the inflammatory and oxidative stress biomarkers, drugs and genetic alterations in the pathophysiologic processes of lung diseases. The recent studies on the analysis of EBC from both a genetic and epigenetic point of view were searched from database and reviewed. This review provides an overview of the current findings in the tracking of genomic and epigenetic alterations which are potentially effective in better management of cancer detection. In addition, respiratory microbiota DNA using EBC samples in association with pulmonary disease especially lung cancer were investigated. Various studies have concluded that EBC has a great potential for analysis of nuclear and mitochondrial DNA alterations as well as epigenetic modifications and identification of respiratory microbiome. Next-generation sequencing (NGS) based genomic profiling of EBC samples is recommended as a promising approach to establish personalized based prevention, diagnosis, treatment and post-treatment follow-ups for patients with lung diseases especially lung cancer.